Penatalaksanaan Relaksasi Otot Progresif : Pursed Lip Breathing dan Respiratory Muscles Stretch Gymnastics dengan Ketidakefektifan Pola Napas Pasien PPOK di Desa Mojolaban Kabupaten Sukoharjo - Novita Siti Fatimah; Deden Dermawan (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a disease characterized by airflow obstruction in the airways (lungs) that is not fully reversible (PDPI, 2011). The prevalence of COPD in Indonesia according to Riskesdas (2013) reaches 3.7% or around 9.2 million people. Measures to overcome the ineffectiveness of non-pharmacological breathing patterns are by practicing progressive muscle relaxation breathing techniques: pursed lip breathing exercise and respiratory muscle stretch gymnastics. The purpose of this action was to describe the management of progressive muscle relaxation: pursed lip breathing exercise and respiratory muscles stretch gymnastics with nursing problems of ineffective breathing patterns in COPD patients. The researcher uses a qualitative method with a case study approach. The technique of taking the research subject is non-probability sampling with a purposive sampling approach. The study population was 3 subjects with COPD. The results of the study. Subjects said that they felt less short of breath, were not use nostril breathing, were not use mouth breathing, respiration was in the normal range (16-20 times/minute). The conclusion was that the provision of progressive muscle relaxation exercises: pursed lip breathing exercise and respiratory muscles stretch gymnastics is effective for overcoming the problem of ineffective breathing patterns in COPD patients.